Mutual coupling reduction in planar antenna by graphene metasurface for THz application. Issue 18 (12th December 2017) - Ghosh, Jeet; Mitra, Debasis
Abstract: This paper presents an effective approach to mitigate mutual coupling between two densely packed planar antenna operating at the lower THz frequency band by incorporating a graphene-based metasurface. The graphene metasurface has been designed using Electric inductive capacitive (ELC) resonator on the both sides of a silicon substrate. The metasurface is designed to provide band stop functionality in the operating bandwidth of the antenna. Here, surface impedance model of the graphene is used for analysing the metasurface layer. Throughout the operating band of the antenna, coupling suppression of 8–12 dB is obtained with element separation of less than . Thus, this proposed approach can be utilized to mitigate mutual coupling between antennas in THz application.